¿Rainbow washing o respeto e inclusión de la diversidad sexual en el Perú? - De la Torre, Luis Arturo (2020)
It is common knowledge that since 2015, Facebook profiles with a gay flag filter have proliferated. This trend was quickly adapted by different brands on their social networks during each month of June (pride month), which gives the impression that inclusion is even greater than previously believed. However, when can you draw the line between a really committed company and one that only uses what is called rainbow washing to attract more customers during the month of June? What is the difference between a social responsibility action and a net sales increase action? In this document, we will analyze the commitment of some companies in Latin America (through advertising, social networks and corporate practices) and we will compare them to question whether their actions are really coherent.